Online Education during Covid-19: Study on the digital literacy of the educational community in Spain - Fernández-Pacheco García, Alejandro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
After the serious events suffered in 2020 due to the appearance of Covid and its subsequent lock-in, educational centers were forced to modify their traditional methodologies in order to carry out an adequate teaching-learning process. The main objective of this study is to know the degree of digital literacy of the educational community, i.e. whether teachers, students and parents of students have sufficient skills to be competent in the use of new technologies adapted to the educational environment.